FORMULASI MASKER GEL PEEL-OFF EKSTRAK ETANOL KULIT BUAH JERUK MANIS (Citrus sinensis (L.) Osbeck) SEBAGAI OBAT JERAWAT - Ariani, Lilies Wahyu; Wigati, Dyan (Media Farmasi Indonesia, 2016)
ABSTRACT Acne is a skin disease keratinization disorder and inflammation caused by the bacterium Staphylococcus aureus. Sweet orange (Citrus sinensis (L.) Osbeck) is one of the plants that can be used as an antimicrobial. This research aims to make preparations gel peel-off mask ethanol extract of sweet orange peel as an acne medicine and evaluate the physical properties as well as antibacterial activity against S. aureus. Gel formulations peel-off mask ethanol extract of sweet orange peel extract was made with varying concentrations of 15%, 25% and 35%. Gel peel-off masks tested in terms of physical properties, namely organoleptic, homogeneity, pH, dispersive power, time dries and viscosity. Antibacterial activity test was conducted using wells. Data were analyzed by one-way ANOVA with 95% confidence level. The results showed that the peel- off mask gel has antibacterial activity with an average diameter of zone 15% inhibitory concentration (1.349 cm), a concentration of 25% (1.69 cm), the concentration of 35% (2.034 cm), the positive control (2.769 cm ) and negative controls (1.1 cm). Statistical analysis showed that the increased concentration of the extract in the formula effect was significantly (p <0.05) on the antibacterial activity.